Advertisement Exposure and Investment Interest: Study on Octafx Advertising Trading Platform among Students - Halim, Umar; Febriyanti, Miranda; Hidayat, Nurul (JURNAL LENSA MUTIARA KOMUNIKASI, 2023)
Some trading platforms are declared illegal, and since 2016 until now the Ministry of Communication and Informatics (Kominfo) has blocked a lot of illegal investment content, especially those using binary options trading systems because they are considered similar to gambling systems. Nevertheless, advertising impressions of trading platforms with binary options systems such as OctaFX can still be found by the public through advertisements on online media such as Youtube. Where advertising has become part of an e-marketing strategy that is considered more effective and efficient at a minimum cost but gets a lot of attention from the target audience. Therefore, this study aims to test the impact of OctaFX trading platform advertising exposure on students' interest in investing in Youtube ads. This research uses stimulus-response theory where advertising is used as variable X and investment interest as variable Y. This study uses an explanatory quantitative approach, with data collection techniques by distributing questionnaires to one hundred student respondents in South Jakarta. The results of this study indicate that exposure to advertisements for one of the trading platforms, namely OctaFx on the online media Youtube, significantly affects the level of interest of students in South Jakarta in investing through this trading platform.